2023
DOI: 10.1186/s13024-023-00605-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phospho-tau in Alzheimer’s disease: towards diagnostic and therapeutic trial applications

Abstract: As the leading cause of dementia, Alzheimer's disease (AD) is a major burden on affected individuals, their families and caregivers, and healthcare systems. Although AD can be identified and diagnosed by cerebrospinal fluid or neuroimaging biomarkers that concord with neuropathological evidence and clinical symptoms, challenges regarding practicality and accessibility hinder their widespread availability and implementation. Consequently, many people with suspected cognitive impairment due to AD do not receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 104 publications
2
27
0
Order By: Relevance
“…Whilst previous studies have shown good biomarker accuracies for plasma p-tau217 17, 20 , performances among CU participants in population-based cohorts have been scanty and in the few available papers the results have been less consistent 6, 12, 34 . This can be mainly attributable to the weak analytical performance (e.g., lack of quantifiable signals, poor precision) of first-generation p-tau217 assays in individuals with very low concentrations including CU participants and those in early symptomatic stages 2, 3 . However, detection of incipient Aβ pathology in the early stages of the AD continuum is crucial not only for early disease identification but also to determine eligibility for the recently approved anti-amyloid therapies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whilst previous studies have shown good biomarker accuracies for plasma p-tau217 17, 20 , performances among CU participants in population-based cohorts have been scanty and in the few available papers the results have been less consistent 6, 12, 34 . This can be mainly attributable to the weak analytical performance (e.g., lack of quantifiable signals, poor precision) of first-generation p-tau217 assays in individuals with very low concentrations including CU participants and those in early symptomatic stages 2, 3 . However, detection of incipient Aβ pathology in the early stages of the AD continuum is crucial not only for early disease identification but also to determine eligibility for the recently approved anti-amyloid therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the evaluation of individuals in early stages of the AD continuum continues to be difficult partly due to heterogeneity in how clinical manifestations compare with biological evidence of disease 4, 5 . The implementation of peripheral biomarkers that can provide biochemical evidence of early AD biological changes could help clinicians to provide specialised diagnostic and/or therapeutic care 2, 3 . In the era of new anti-amyloid-beta (Aβ) immunotherapy drugs for AD, early intervention will be critical for maximising treatment efficacy, and robust biomarkers that become abnormal in cognitively unimpaired individuals as well as patients in the early symptomatic phases will be essential for first-in-line screening of patients eligible for treatment 5, 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have sought plasma biomarkers relevant to AD diagnosis, and the past decades have seen several analytes being tested for this purpose 51 . For example, recent studies have demonstrated that AD hallmarks in plasma such as Aβ42/40, p‐tau181, p‐tau231, and p‐tau217 can identify brain pathology with high accuracy, further adding significant weight to the growing body of evidence in their use as a non‐invasive diagnostic tool for AD 52–54 . Apart from AD hallmarks in blood, an increasing number of studies have discovered a range of other proteins and metabolites in plasma that might also act as diagnostic biomarkers 55,56 .…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%